(untitled) (European Journal of Pure and Applied Mathematics, 2023)
This paper present results of ω-order preserving partial contraction mapping generating a general class of semilinear initial value problems. We consider the use of fractional powers of unbounded linear operators for its application by starting with some results concerning such fractional powers. We assume A to be the infinitesimal generator of an analytic semigroup in a Banach space X, 0 ∈ ρ(A) and defined the fractional powers of A for 0 < α ≤ 1. We also show that Aα is a closed linear operator whose domain D(Aα) ⊃ D(A) is dense in X. Finally we established that the operator is bounded, continuous and Holder continuous.